2005
DOI: 10.1158/0008-5472.can-05-2059
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of Krüppel-Like Factor 4 Protein in Response to Serum Stimulation Involves the Ubiquitin-Proteasome Pathway

Abstract: Although the zinc finger transcription factor Krüppel-like factor 4 (KLF4) has been shown to be a negative regulator of cell proliferation, the mechanisms underlying the posttranslational modification of KLF4, especially at the level of protein degradation, are poorly understood. Here, we show that KLF4 protein levels in quiescent cells were high, but decreased rapidly as cells entered the proliferating stage following serum stimulation. This decrease was partially reversed by pretreatment with MG132, a protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 39 publications
2
78
0
Order By: Relevance
“…: (25)(26)(27)(28)(29)(30)(31)(32). Because of its known role as a transcription factor, we sought to systematically determine how it interacted with the IL-6 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…: (25)(26)(27)(28)(29)(30)(31)(32). Because of its known role as a transcription factor, we sought to systematically determine how it interacted with the IL-6 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Cycloheximide Chase Assay-The cycloheximide chase assay was performed as described (81,82). Briefly, HEK293T cells were transfected with either pCMV-Myc-KLF4 or pCMVMyc-KLF4-K275R, treated with 100 g/ml cycloheximide, and lysed at the indicated time points.…”
Section: Methodsmentioning
confidence: 99%
“…The oncogenic effect of KLF4 has been reported in breast and squamous cell carcinoma [243][244][245][246][247], while its tumor suppression role was reported in various types of cancers such as colon cancer [248,249]. It was demonstrated that KLF4 is a fast turnover protein, whose turnover-half life is governed by the ubiquitin-proteasome system [250,251]. Several e3 ligases such as APC/CDH1 and CUL2/vHL have been linked to the turnover of KLF4 in response to different signaling [224,252].…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%